Dinamika Kepribadian Tokoh Kolo Dalam Novel Benang Merah Karya Unu Ruben Paineon (Kajian Psikoanalisis Sigmund Freud) - Katarina Derici Siki; Vincentius Mauk; Giri Indra Kharisma (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
The research on the novel 'Benang Merah' by Unu Ruben Paineon tells the story of the life journey of the character Kolo during his childhood, who always remembers the shadow of his father's death until he grows up. Therefore, this study utilizes literary psychology theory, specifically Sigmund Freud's psychoanalysis, to examine Kolo's personality structure and defense mechanisms. The aim of the research is to describe the personality structure and defense mechanisms of the character Kolo. The research method used is qualitative descriptive method because this study is more inclined towards description based on the research object presented through words or sentences in the novel 'Benang Merah' according to the problem formulation. The analysis of the personality structure of the main character revealed the presence of id, ego, and superego, with each structure consisting of 3 data points discovered. The defense mechanisms show the existence of repression, sublimation, projection, displacement, rationalization, reaction formation, regression, aggression, and fantasy, with each mechanism consisting of 1 data point.